Guava - Hodge, W. (Stephens Ltd., Trinidad, 2009)
A picture of a bunch of Guava on a branch. The fruit are not only relished by humans, but by many mammals and birds as well. The spread of introduced guavas owes much to this fact, as animals will eat the fruit and disperse the seeds in their droppings.
Colour: Coloured; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Fruit--Trinidad and Tobago; Guava--Trinidad and Tobago